The impact of intellectual capital and company risk on stock returns with size as a moderator - Permatasari, Novelia Kiki; Dasmaran, Verliani; Tatang, Tatang (Institute of Accounting Research and Novation (IARN), 2025)
This study aims to investigate the interaction between Intellectual Capital and company risk in influencing stock returns, as well as how company size may moderate this relationship. By gaining a deeper understanding of these dynamics, companies are expected to make more informed decisions regarding the management of Intellectual Capital, risk management, and the optimization of stock returns. The primary objective is to assess the impact of Intellectual Capital and company risk on stock returns, and to determine whether company size strengthens or weakens the relationship between these factors and stock returns. The research employs a quantitative approach, focusing on manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange from 2021 to 2023. The sample is selected using purposive sampling, and data analysis includes Multiple Linear Regression, Correlation, and Determination tests. The data is processed using the Eviews 12 statistical tool. The findings reveal that Intellectual Capital significantly affects stock returns, while company risk does not have a significant impact. Additionally, company size enhances the influence of Intellectual Capital on stock returns, but does not moderate or weakens the effect of company risk on stock returns.